2022
DOI: 10.1080/21645515.2021.2013694
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of COVID-19 vaccine hesitancy in the age of infodemic

Abstract: Background Addressing COVID-19 vaccine hesitancy is key to ending the COVID-19 pandemic. Communication and media environments are potential drivers of vaccine hesitancy. It is worthwhile to examine the relationship between social media use and COVID-19 vaccine hesitancy. Objective This study aims to understand the prevalence and determinants of COVID-19 vaccine hesitancy. Methods Questionnaires were administered to 463 participants in mainlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
21
1
1
Order By: Relevance
“…This probably could reflect the trust of the elderly in biased, inappropriate, and fake information available on online platforms. In fact, the recent study also confirmed that people's vaccine acceptance or hesitancy was highly influenced by the information distributed in social media ( 24 , 28 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This probably could reflect the trust of the elderly in biased, inappropriate, and fake information available on online platforms. In fact, the recent study also confirmed that people's vaccine acceptance or hesitancy was highly influenced by the information distributed in social media ( 24 , 28 ).…”
Section: Discussionmentioning
confidence: 74%
“…The vaccination is the most appropriate approach for preventing and spreading COVID-19. However, peoples' perceptions toward vaccine effectiveness have fluctuated with the information flow on various social media channels and the severity of COVID cases ( 24 , 25 ). Therefore, it is important that the current scenario of peoples' perception toward vaccine effectiveness and determinants affecting the same be explored to promote the vaccination approach against COVID-19 prevention and transmission effectively.…”
Section: Discussionmentioning
confidence: 99%
“…For both time periods, 17 studies that compared women vs. men reported that men were more likely to accept the COVID-19 vaccine [41] , [43] , [46] , [47] , [52] , [56] , [61] , [62] , [65] , [72] , [74] , [75] , [76] , [81] , [83] , [85] , [88] ; however, in four studies, women were more likely to accept the COVID-19 vaccine [39] , [75] , [86] , [93] . Older age was associated with increased COVID-19 vaccine uptake compared to younger age [35] , [38] , [50] , [52] , [53] , [57] , [64] , [74] , [75] , [76] , [85] , [86] , [90] , [92] , [95] , [100] , and this result was stable across the time periods, with six studies reporting higher uptake in younger age groups [39] , [43] , [47] , [62] , [65] , [94] . Across both periods, 18 studies found that education levels correlated positively with COVID-19 vaccine uptake [35] , [46] , [49] , [52] , [53] , [57] , [59] , [60] , [63] , [67] , [68] , [74] , [76] , [85] , [88] , [90] , …”
Section: Resultsmentioning
confidence: 99%
“…Vaccine-refusing HCWs with less than a college degree reported that their decision to refuse the COVID-19 vaccine was motivated by their social media network, which was different from vaccine refusers with a college degree or higher. Previous research documented a link between social media and greater vaccine hesitancy [65][66][67], but it is unknown how educational level affects the relationship between social media networks and vaccine hesitancy in HCWs.…”
Section: Educationmentioning
confidence: 99%